FORMATION OF SYSTEMATIC THINKING IN FUTURE BIOLOGY TEACHERS (American Journal of Pedagogical and Educational Research, 2023)
This article was written in order to consider the topic "Formation of systematic thinking in biology teachers". This article discusses how biology teachers can work with systems thinking and how this thinking can benefit their students. The article talks about systematic thinking, teaching technologies, exchange of experience, relationships between teachers and students and other indicators. The article presents systems thinking practices for biology teachers and provides information on how to apply and implement them. The article is useful for teachers and makes their students comfortable.